3D RECONSTRUCTION WITH ABSOLUTE SCALE USING A MONOCULAR CAMERA - Mahendra Widya Putra, Ronggur
This research develops an absolute scale 3D reconstruction system using a monocular camera and ChArUco Board markers. Monocular cameras face the significant challenge of scale ambiguity as they only capture two-dimensional information without explicit data on the actual distance between the camera and the object. This results in 3D models with relative scales that are inaccurate in terms of absolute size and distance. The method involves using ChArUco Board markers for absolute scale calibration, the Structure from Motion (SfM) algorithm for 3D reconstruction, and optimization using Bundle Adjustment. Markers are placed around the object to provide known size references, allowing the system to calibrate the 3D model's scale. The research results show that this system achieves up to 95% accuracy in absolute scale, with 3D prints showing a high degree of similarity in size and proportion to the original objects. The evaluation was conducted by comparing the reconstructed point cloud with the ground truth point cloud using point cloud similarity metrics such as Hausdorff Distance. The evaluation results indicate that the Hausdorff Distance does not exceed 0.05, indicating that the difference between the reconstructed model and the original object is minimal. In conclusion, the use of markers as external references successfully overcomes the scale ambiguity problem in 3D reconstruction using monocular cameras, opening up practical application possibilities in various fields that were previously unattainable.